Conservatism Accountancy, Profit Persistence and Systematic Risk Towards the Earnings Responses Coefficient - Sri Agustina Basuki; Aida Nahar; Muhammad Ridho (Faculty of Economics, Universitas Sriwijaya, 2017)
The purpose of this research is to understand the influence of investor reaction towards profit that measured by the earning response coefficient with the variable of conservatism accountancy, persistence of profit and the systematic risk at the company, which have high market capitalization and listed in the LQ 45 index. Population in the research are companies, which are listed in the LQ 45 index from the period of 2011 to 2015 that have complete financial information, and have financial notation in the form of Rupiah and excluded from the banking sector. The analysis method that being used is multiple linier regressions analysis and the result shows that conservatism accountancy partially significant affecting the Earning Response Coefficient. It shows that there is an investor reaction towards companies in the Index LQ 45, which applies conservatism accountancy in gaining profit. Profit persistence and the systematic risk is not significantly affecting earnings response coefficient.